The Role of Bamus in Nagari Development - Yesi Lila; Fatmariza Fatmariza; Helmi Hasan (Jurnal Aplikasi IPTEK Indonesia, 2018)
The purpose of this research is to analyze the implementation of the role of the Consultative Body (Bamus) and identify the factors that influence the implementation of the role of the Consultative Body (Bamus) in the construction of Nagari Pilubang. The type of research used is descriptive research with qualitative approach by using observation technique, interview and documentation study. The results show that the implementation of the role of members of Bamus in nagari development has not been optimal, it can be seen from the unfinished implementation of legislative function, budget function, supervision function and the function of accommodating and channeling the aspirations of the community. This is due to several factors including the limited human resources of the members of Bamus Nagari, the lack of cooperation, communication and coordination between each member of Bamus, the lack of cooperation and communication between Bamus and the nagari government, KAN and other nagari institutions in terms of official, trial based on provisions that have been established and the last lack of confidence and courage members Bamus in conveying his opinion in public.